Studies in chemical changes during storage of onions (Allium Cepa Linn) - Cabacungan, Judy C. (1975)
Chages in the pungency and reducing sugars content of Yello Granex and Red Creole onion bulbs and in the total anthocyanins content of the latter were investigated during low- and room-temperature storage. Changes in the pungency, color and moisture content of imported and local dehydrated powdered onions during storage at refrigerated and room temperature were also followed. A crate of red Creole onions was stored at 1 ± 1°C and another at 29-31°C. Two (2) half-fulfilled mesh bags of Yellow Granex bulbs were kept at 2 ± 1°C and another pair at6 29-31°C. The dehydrated powdered onions were packed in 5 - by 7.5-cm 4 mil-thick polyethylene pouches, each containing 10g, and placed in large (12.9 cm in diameter and 17.6 cm. high) tin container with insert-in-place end. A container was held at 9-10°C and another 27-28°C. The results of the chemical tests performed during 3 months' storage were analyzed using t-test for paired observations, linear regression and range method of comparing several averages. The pungency, as measured by the per cent transmittance of oxidized onion distillate, of the Red Creole onions studied was found practically unaffected during storage at low and room temperatures. A slight increase in reducing sugars content was noted in the cold-stored Red Creole bulbs, but a significant decrease in the room stored. At both temperatures, storage was accompanied by substantial loss of anthocyanine. Under ordinary conditions, the Yellow Granex onions lasted for only a month. Highly significant reductions in pungency and reducing sugars content were observed at both storage temperatures. The dehydrated powdered onions retained practically the same flavor strength during storage. Absorbance of extracts, as an indication of browning, of the local product increased significantly at room temperature. At both temperatures, considerable moisture absorption by the two kinds of onion powder proceeded.